Reduced anti-Müllerian hormone action in cumulus-oocyte complexes is beneficial for oocyte maturation without affecting oocyte competence - Xu, Fuhua; Bagnjuk, Konstantin; Marti-Gutierrez, Nuria; Srinivasan, Sathya; Mayerhofer, Artur; Lee, David; Pejovic, Tanja; Mitalipov, Shoukhrat; Xu, Jing (Frontiers in Endocrinology, 2024)
Anti-Müllerian hormone (AMH) is a key paracrine/autocrine factor regulating folliculogenesis in the postnatal ovary. As antral follicles mature to the preovulatory stage, AMH production tends to be limited to cumulus cells. Therefore, the present study investigated the role of cumulus cell-derived AMH in supporting maturation and competence of the enclosed oocyte. Cumulus-oocyte complexes (COCs) were isolated from antral follicles of rhesus macaque ovaries for in vitro maturation with or without AMH depletion. Oocyte meiotic status and embryo cleavage after in vitro fertilization were assessed. In vitro maturation with AMH depletion was also performed using COCs from antral follicles of human ovarian tissue. Oocyte maturation and morphology were evaluated. The direct AMH action on mural granulosa cells of the preovulatory follicle was further assessed using human granulosa cells cultured with or without AMH supplementation. More macaque COCs produced metaphase II oocytes with AMH depletion than those of the control culture. However, preimplantation embryonic development after in vitro fertilization was comparable between oocytes derived from COCs cultured with AMH depletion and controls. Oocytes resumed meiosis in human COCs cultured with AMH depletion and exhibited a typical spindle structure. The confluency and cell number decreased in granulosa cells cultured with AMH supplementation relative to the control culture. AMH treatment did not induce cell death in cultured human granulosa cells. Data suggest that reduced AMH action in COCs could be beneficial for oocyte maturation. Cumulus cell-derived AMH is not essential for supporting oocyte competence or mural granulosa cell viability.